A View of Virtual Reality in Learning Process - Al Farsi G.; Tawafak R.M.; Malik S.I.; Mathew R.; Ashfaque M.W. (Springer Science and Business Media Deutschland GmbH, 2023)
VR has a great deal of promise, and its application to education has recently seen a great deal of research interest. However, there is currently little systematic work on how researchers have used immersive VR for higher education purposes, despite the use of both high-end and budget head-mounted displays (HMDs). Therefore, to classify design elements of current research dedicated to VR in higher education, we recommend using systematic mapping. The papers reviewed collected through the extraction of critical information from documents indexed in digital scientific libraries. The settings of VR also represent 3D space, which may be real or fictional, macroscopic or microscopic and based on natural physical laws of physics, or imaginary dynamics. The multiple examples that can use to represent VR make it widely applicable to education in different fields. A primary characteristic of VR is that it allows multi-sensory contact with space to simulate. This paper explores and discusses the view about the virtual reality, the problems, and the challenges faced in the learning process. 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.